Preparation and Catalysis of Pd Loaded PS/Fe3O4@PPy/Pb Magnetic Composite materials. Issue 1 (1st February 2022) - Fang, Xue; Su, Guiming; Jiang, Haijian; Chen, Mingyue; Li, Tianzhi; Song, Meihui; Zhang, Xiaochen
Abstract: Fe3 O4 particles were prepared by chemical co-precipitation method. Then, the functionalized PS nanoparticles were mixed with the prepared Fe3 O4 particles, the PS/Fe3 O4 magnetic nanocomposite were obtained by electrostatic interaction; the pyrrole monomer was added, and the pyrrole monomer undergoes oxidative polymerization on the surface of the composite. The PS/Fe3 O4 @PPy composite coated with polypyrrole was obtained. Finally, the PS/Fe3 O4 @PPy/Pb magnetic composite was prepared by the deposition-precipitation method. The morphology and structure of the composite particles were analyzed by scanning electron microscope, X-ray diffractometer, Fourier transform infrared spectrometer, and thermogravimetric analyzer. The concentration of organic dye molecules was determined by ultraviolet-visible spectrophotometer. The results showed that the dispersion of the PS/Fe3 O4 @PPy/Pb magnetic composite was excellent; the PS/Fe3 O4 @PPy/Pb magnetic composite showed excellent catalytic performance in the reduction of methylene blue with sodium borohydride as reducing agent. The composite could be recycled and reused many times.